A male body as communal space? Engaging sexuality and masculinities from selected sacred texts - Masenya, Madipoane (HTS teologiese studies, 2023)
Expressions such as ‘a piece of a man is better than no man’, and monna ke kobo, re a apolelana [a man is a blanket, he is shared among us] (read: women) afford hearers a small glimpse about female perceptions on a male body and/or male sexuality. Several African proverbs shed light on the underlying assumption that a male body, despite the man’s marital status, can be shared with many women. Also, a glimpse, at certain texts in the Hebrew Bible (cf. Es 2) appears to give readers an impression that a male body, including a married man’s body, can be shared with other women. In a nutshell, patriarchal heteronormativity coupled with unhealthy notions of masculinity, seem to take it for granted that a male body is a collective space, not necessarily for female pleasure in marriage, it may be argued, but first and foremost, for the satisfaction of male desire, the entrenchment of the normativity of the male species as well as the endorsement of dangerous notions of masculinities.Contribution: Can the pursuit for equality, human and/or woman dignity and reciprocity succeed amid the preceding dynamics of the intersection among power, male sexuality and unhealthy notions of masculinities as revealed in the affirmation and celebration of the notion of the ‘male body as communal space’ especially in the context of heterosexual unions? The preceding was the main question that this essay sought to answer.